Impacts of the leader team exercise on team performance - Hilton, Bradley C. (Kansas State University, 2014)
In today’s interconnected world, teams must form quickly, learn and adapt to overcome challenges regardless of the environment. For example, complexity in responding to natural disasters or man-made political, economic and security crises often requires the ability to learn collaboratively to minimize human suffering and protect property. When teams find success, the operation succeeds beyond what a single organization can provide, but when teams fail they can make a bad situation worse. Leveraging an approach called a Leader Team Exercise (LTX), teams can generate the shared qualities of understanding, confidence and competence in a structured manner to accelerate learning and performance. This research study investigated the potential of an LTX through initial research in a within-subjects experimental design of the 161st Artillery Battalion, Kansas Army National Guard as they negotiated obstacles located on the Fort Riley, Kansas Field Leaders Reaction Course (FLRC). The quantitative data collected was evaluated employing non-parametric statistical tests to answer five research questions about the relationship of the LTX to dependent variables of team performance, shared understanding and shared confidence to further explore field observations of learning action teams. The study provides new knowledge to further advance understanding of the LTX and its relationship to team performance and learning. In addition, the study also offers a source of data as a foundation for future research to continue investigation into the full depth and breadth of the LTX in other settings and conditions. The study found a relationship among the dependent variables and the FLRC, as well as a relationship between the LTX and team demographics related to shared understanding and performance. The findings also advance the adult education body of knowledge about learning dynamics, which occur outside the classroom. The implications to improve teams that rapidly form, disband, and form again will impact adult learning in a wide spectrum of applications in the government, academia and industry. Finally, the study offers recommendations for future areas of research and practical application based on current knowledge for the Kansas National Guard and others who might use or plan on using the LTX in the future.
Keywords: Team learning; Collaboration; Military studies; Adult Education (0516)